Using Serious Games to Train Children and Elicit Fire Safety Behaviour - Almeida, João E. (2019)
Serious Games are being increasingly used as a tool for various applications, contrary to the traditional entertainment purpose. One of their application domains is fire safety. Possible injuries from fires are a dangerous safety concern for children, for instance. Another important issue is the elicitation of behavioural knowledge to design and feed simulation models. The lack of human behaviour data is often referred to as a drawback to evacuation simulation designers. This paper addresses the aforementioned matters in respect to: i) acquiring valuable knowledge on children behaviour when facing the urgent need for evacuation; and ii) devising an educational tool. A group of 19 children from an elementary school played two different role plays using a Serious Game and the data of their behaviours was collected. Results were analysed and are here presented. Future work is two-fold: to expand and to refine data collection to other groups such as elderly; to use this data for crowd synthesis particularly for evacuation simulators.